2001
DOI: 10.1016/s0029-7844(00)01088-7
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical artery N-terminal peptide of proatrial natriuretic peptide in hypertensive pregnancies and fetal acidemia during labor

Abstract: In groups 1-3, N-terminal peptide of proatrial natriuretic peptide concentrations were higher (P <.001) than in the control group. In group 1, neonates with abnormal umbilical artery blood velocity pattern had higher N-terminal peptide of proatrial natriuretic peptide concentrations than neonates with normal umbilical artery Doppler findings (P <.006). N-terminal peptide of proatrial natriuretic peptide concentrations were higher in group 2 (P <.002) than in groups 1 and 3. CONCLUSIONS Maternal hypertensive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…showed that umbilical‐cord ANP level was inversely related to UA pH. Maternal hypertensive disorder and fetal acidemia during labor have been reported to stimulate fetal ANP production. We found that a UA pH of < 7.15 is correlated independently with high NP levels, which is consistent with the findings of these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…showed that umbilical‐cord ANP level was inversely related to UA pH. Maternal hypertensive disorder and fetal acidemia during labor have been reported to stimulate fetal ANP production. We found that a UA pH of < 7.15 is correlated independently with high NP levels, which is consistent with the findings of these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…1626 (402-9574) pmol/L, P = 0.0001). NT-proANP values of all neonates with a CVP score ≤ 6 were above the 95 th percentile NT-proANP value of normal pregnancies, while 42 of 67 (63%) fetuses with CVP > 6 had NT-proANP concentrations above the 95 th percentile value in normal pregnancies 13 . The fetuses with umbilical venous pulsations had higher umbilical artery mean (SD) NT-proANP values than had fetuses with a normal nonpulsatile umbilical venous blood flow profile (6580 (5833) pmol/L vs. 2131 (1671) pmol/L, P < 0.0001).…”
Section: Resultsmentioning
confidence: 78%
“…29 There is no significant transplacental passage of NT-proANP, and mode of delivery does not influence UA plasma ANP concentrations. 4,30 In addition, atrial natriuretic factor concentrations do not change with gestation. 31 Gestational age at delivery and mode of delivery do not affect newborn cTnT levels, at least after 27 weeks' gestation.…”
Section: Mäkikallio Et Al Fetal Echocardiography and Biochemical Markmentioning
confidence: 97%
“…Concentrations of fetal NT-proANP and cTnT (Enzymum-Test Troponin-T, Boehringer Mannheim Diagnostics) were determined. 4,5 We previously found that in neonates born after uncomplicated pregnancy and labor, the ϩ2 SD level of NT-proANP was 1145 pmol/L 4 , which was chosen to represent the cut-off level. A clinically significant cTnT concentration was set at 0.10 ng/mL 5 .…”
Section: Biochemical Markers Of Cardiac Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation